Household food insecurity and nutritional status of toddler in Central Lombok. - Khairul Abdi, Lalu; Lalu Juntra Utama; I Gde Narda Widiada; Lina Yunita (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: Food insecurity can cause nutritional problems, especially in toddlerhood, where at this time nutritious intake is needed because at this time children experience growth that can have an impact on their adulthood. Food insecurity can stem from income poverty which negatively impacts overall household consumption levels. Therefore, the condition of food insecurity causes malnutrition so the purpose of this study is to assess household food insecurity and nutritional status of toddlers in central Lombok, West Nusa Tenggara. Methods: The design of this research was a cross-sectional study; data collection was carried out in Central Lombok Regency, West Nusa Tenggara Province, Indonesia. This research involved two groups of subjects: toddlers and father or mother caregiver. The total number of subjects was 391 toddler include the household . Subjects were taken at each community health center using a simple random method without replacement. All primary data was collected through an interview process using a structured questionnaire and direct measurements. The analysis process for all types of data was carried out with the help of the SPSS for Windows program with the Pearson correlation test and One Way Anova test. Results: This study presents that as many as 60.1% of households in Central Lombok experience food insecurity at mild, moderate and severe levels. Which can be caused by due to low monthly household income and social assistance. Although the results of the analysis showed that no significant relationship was found (p>0,05) between the household food insecurity score and the anthropometric of the nutritional status of the toddlers almost half of the undernourished toddlers were included in the food-insecure. Conclusions:. High rate of food insecurity that occurs then, for increased access to food especially during period of rapid development and growth to overcome malnutrition so that can prevent bad impact in the future.